(untitled) - Food and Agriculture Organization of the United Nations (Rome, 2008)
FAO produced Guidelines for the Ecolabeling of Fish and Fishery Products from Marine Capture Fisheries. Those guidelines were adopted by the twenty-sixth session of COFI in 2005. In 2006 FAP held an Expert Consultation on the development of similar guidelines for inland capture fisheries. In adopting the guidelines, the twenty-sixth session of COFI recommended that "FAO should review and futher develop general criteria in relation to 'stock under consideration' and to serious impacts of the fishery on the ecosystem. This recommendation was subsequently endorsed by the twenty-seventh session of COFI in March 2007, where it was agreed that FAO undertake further work in relation to minimum substantive requirements and criteria for both marine and inland capture fisheries. The expert Consultation reviewed the existing marine and inland capture fisheries guidelines and formulated recommendation to COFI to address COFI's request on "stock under consideration" and "minimum substantive requirements".
Keywords: Sản phẩm cá,Ecosystems,Hệ sinh thái,Fishery products